1994
DOI: 10.1002/pen.760340507
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical analysis and its relationship to impact transitions

Abstract: Detailed, instrumented impact tests were carried out between about − 100 and 60°C for flexible poly(vinyl chloride) (PVC), ethylene vinyl acetate (EVA), and polypropylene (PP) films. Secondary impact transitions in addition to the main transitions were detected for all three films, indicating that multiple impact transitions may be far more general in occurrence than commonly expected. Wide frequency (from 0.05 to 100 Hz) dynamic mechanical spectra of the same materials were also generated over similar tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Recently there has been a revival of the interest in homogeneous copolymers because of catalytic developments in this field. In particular by metallocene catalysis [18][19][20][21][22][23] in combination with specific polymerization processes a new class of homogeneous copolymers are currently being developed with properties different from those of the existing heterogeneous copolymers.…”
Section: --4466/96/$ 5 O0 9 1996 Akaddmiai Kiadd Budapest John mentioning
confidence: 99%
“…Recently there has been a revival of the interest in homogeneous copolymers because of catalytic developments in this field. In particular by metallocene catalysis [18][19][20][21][22][23] in combination with specific polymerization processes a new class of homogeneous copolymers are currently being developed with properties different from those of the existing heterogeneous copolymers.…”
Section: --4466/96/$ 5 O0 9 1996 Akaddmiai Kiadd Budapest John mentioning
confidence: 99%
“…More specifically, it was suggested that polymers possessing low temperature secondary transitions, especially those related to main‐chain motions, would display good impact toughness at room temperature. The proposed connection was based on the similarity in the position and activation enthalpy of fracture mode transitions and secondary loss transitions 12–18. There are, however, also numerous exceptions to the rule 11, 19…”
Section: Introductionmentioning
confidence: 99%
“…The relevant relaxation processes are the first secondary relaxation below T g . Hartmann and Lee [17] and Woo et al [18] had reported a method that by doing a Fourier analysis to obtain the complete frequency spectrum of the impact pulse and comparing this spectrum with the room-temperature frequency spectrum of the loss factor of the secondary transition, the impact resistance was correlated with the secondary transition. They also obtained good agreement between the calculated value and the measured value.…”
Section: Introductionmentioning
confidence: 99%